2016
DOI: 10.21037/atm.2016.06.14
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors and risk of dementia

Abstract: Background: Proton pump inhibitors (PPIs) are one of the most commonly prescribed medications. Recent studies have raised a concern over increased risk of dementia among PPIs users but the results of those studies were inconsistent. We conducted this systematic review and meta-analysis to summarize all available data.Methods: A literature search was performed in MEDLINE and EMBASE database from inception to April 2016.Observational studies that reported risk of dementia among PPIs users compared with non-users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…This was the same conclusion as other large studies [3]. However, recently, Gray et al [4] reported that PPI use is not associated with dementia risk, even for people with high cumulative exposure in a prospective population-based study.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…This was the same conclusion as other large studies [3]. However, recently, Gray et al [4] reported that PPI use is not associated with dementia risk, even for people with high cumulative exposure in a prospective population-based study.…”
supporting
confidence: 83%
“…Over the past decade, the use of PPIs in society is increasing, especially in the elderly, as they are generally regarded as safe medications with very few adverse effects. There is a well-recognized epidemiological link between PPIs and the increased risk of dementia [2, 3]. However, many studies have reported that PPIs are not associated with a greater risk of dementia or AD [4, 5].…”
mentioning
confidence: 99%
“…Those therapeutic options are effective; however, when the patients remain under daily stress, poor diet, alcohol abuse and nonsteroidal anti‐inflammatory drugs consumption, smoking habit, and persistent infection by H. pylori , the ulcer recurrence is very frequent . Therefore, to avoid this problem, many patients use antisecretory drugs continuously, mainly PPIs, which lead to the side effects related to these drugs, including neoplastic lesions , osteoporosis , or increased risk of dementia . Thereby, the development of new or adjuvant antiulcer drugs, most effective and with less adverse effects, is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found the biological feasibility of the association between PPI use and cognitive impairment in murine models. This may have implications for human beings, as has been observed in developed countries where research has been conducted on PPIs and their positive association with cognitive impairment, as shown in this study in the Latin American context, where information on the subject is limited (6,9).…”
Section: Discussionmentioning
confidence: 75%